ANALISIS KUALITATIF POLA PARTISIPASI SISWA KELAS II PADA MATERI NILAI-NILAI PANCASILA MELALUI PENERAPAN METODE TALKING STICK DI SDN BANJARBENDO - Naufal Achmad Fakhruz Syahdam; Achmad Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the participation patterns of second-grade students in Pancasila Education learning on the topic of Pancasila Values through the implementation of the Talking Stick method at SDN Banjarbendo. The study was motivated by the varying levels of student participation in classroom learning, particularly in terms of speaking confidence and involvement during learning activities. The Talking Stick method was selected because it provides equal opportunities for students to speak and actively engage in the learning process. This research employed a qualitative approach using a case study design. The participants consisted of second-grade students, the classroom teacher, and the school principal. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that student participation patterns were manifested in two main forms: verbal and nonverbal participation. Verbal participation was reflected in students’ ability to answer questions, express opinions, and respond to learning materials. Based on the intensity of involvement, verbal participation was categorized into active, moderate, and low levels. Meanwhile, nonverbal participation was demonstrated through attention to teachers and peers, eye contact, enthusiastic expressions, readiness to receive the talking stick, and physical responses during learning activities. The Talking Stick method created a more interactive learning environment, provided equal speaking opportunities, and encouraged students’ engagement in understanding and applying Pancasila values. Therefore, the Talking Stick method contributed to fostering a more participatory and meaningful Pancasila Education learning process.